2013
DOI: 10.1503/jpn.120232
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fixation to eyes during facial emotion labelling in children with bipolar disorder or severe mood dysregulation

Abstract: IntroductionSevere mood disorders in children, specifically bipolar disorder (BD) and severe mood dysregulation (SMD), have recently received increased attention, as researchers and clin icians acknowledge the substantial impairment and treatment needs of these populations. The BD and SMD phenotypes differ in that BD is characterized by distinct episodes of mania (and, frequently, depression), whereas SMD is characterized by severe, chronic, impairing irritability.1 Importantly, however, the 2 phenotypes are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 61 publications
0
16
2
1
Order By: Relevance
“…In addition, the association between CDI scores and emotion recognition was significant even after accounting for current irritability symptoms, with the latter not being associated with emotion recognition accuracy. These findings contrast with previous studies in which, compared with healthy volunteers, deficits in emotion recognition were found in youth with severe irritability (Deveney et al., ; Guyer et al., ; Kim et al., ; Rich et al., ). The discrepancy with previous studies may be explained by different operating definitions of chronic severe irritability, that is, previous works have employed youth with severe mood dysregulation, which encompasses hyperarousal symptoms, and includes sadness along anger as negative mood.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, the association between CDI scores and emotion recognition was significant even after accounting for current irritability symptoms, with the latter not being associated with emotion recognition accuracy. These findings contrast with previous studies in which, compared with healthy volunteers, deficits in emotion recognition were found in youth with severe irritability (Deveney et al., ; Guyer et al., ; Kim et al., ; Rich et al., ). The discrepancy with previous studies may be explained by different operating definitions of chronic severe irritability, that is, previous works have employed youth with severe mood dysregulation, which encompasses hyperarousal symptoms, and includes sadness along anger as negative mood.…”
Section: Discussioncontrasting
confidence: 99%
“…The discrepancy with previous studies may be explained by different operating definitions of chronic severe irritability, that is, previous works have employed youth with severe mood dysregulation, which encompasses hyperarousal symptoms, and includes sadness along anger as negative mood. Differences could also be attributed to the use of distinct tasks (Kim et al., ; Rich et al., ), less conservative analyses (Deveney et al., ; Guyer et al., ), distinct features of examined emotion labeling accuracy (Kim et al., ; Rich et al., ), or simply because the effects of depressive symptoms on emotion recognition were not tested or could not be tested (Guyer et al., ; Kim et al., ; Rich et al., ). Nevertheless, our longitudinal analysis showed that regardless of current depressive symptoms, emotion recognition deficits in youth with DMDD—who mostly had low depressive symptoms at baseline—were predictive of more depressive symptoms at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deviations from characteristic spatial or temporal eye-movement patterns to faces have been shown to reflect disorders including autism spectrum disorders (Kliemann, Dziobek, Hatri, Steimke, & Heekeren, 2010; Klin, Jones, Schultz, Volkmar, & Cohen, 2002; Morris, Pelphrey, & McCarthy, 2007; Pelphrey et al, 2002; Pelphrey, Morris, & McCarthy, 2005; Snow et al, 2011), schizophrenia (Green, Williams, & Davidson, 2003a, 2003b; Manor et al, 1999; M L Phillips & David, 1997; Mary L. Phillips & David, 1997, 1998; Streit, Wölwer, & Gaebel, 1997; Williams, Loughland, Gordon, & Davidson, 1999), bipolar disorder (Bestelmeyer et al, 2006; E. Kim et al, 2009; P. Kim et al, 2013; Loughland, Williams, & Gordon, 2002; Streit et al, 1997), and prosopagnosia (Schwarzer et al, 2007; Stephan & Caine, 2009; Van Belle et al, 2011), among others (Horley, Williams, Gonsalvez, & Gordon, 2003, 2004; Loughland et al, 2002; Marsh & Williams, 2006), and are thought to relate to the social and perceptual deficits associated with such disorders (e.g., see the correlation of eye-region fixations to emotion recognition performance for children with bipolar disorder, but not for healthy control children, reported in P.…”
Section: - Introductionmentioning
confidence: 99%
“…Kim et al, 2009; P. Kim et al, 2013; Loughland, Williams, & Gordon, 2002; Streit et al, 1997), and prosopagnosia (Schwarzer et al, 2007; Stephan & Caine, 2009; Van Belle et al, 2011), among others (Horley, Williams, Gonsalvez, & Gordon, 2003, 2004; Loughland et al, 2002; Marsh & Williams, 2006), and are thought to relate to the social and perceptual deficits associated with such disorders (e.g., see the correlation of eye-region fixations to emotion recognition performance for children with bipolar disorder, but not for healthy control children, reported in P. Kim et al, 2013).…”
Section: - Introductionmentioning
confidence: 99%